Pembelajaran IPA terkait Materi Bom Atom dan EfekPenggunaannya Menggunakan Pendekatan Psikologis Naratif - Susdarwono, Endro Tri (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2021)
This study aims to compare science learning using conventional methods and narrative psychological approaches regarding atomic matter and atomic nuclear, fission reactions, atomic bombs, and the effects of atomic bomb radiation. In this study the method used is experimental. While the approach in this study used is quantitative. The quantitative approach used includes hypothesis testing with Wilcoxon stratified numbers. Hypothesis testing with the number of Wilcoxon stratified levels was used as an analysis to determine the comparison between two groups of samples that were treated differently and grouped into certain strata. This method is a further development of the hypothesis testing method with the number of Wilcoxon levels. Based on the calculations, this study concludes that there are differences in learning performance, learning using narrative psychological approaches related to atomic bomb material and the effect of using atomic bombs has better performance than conventional learning methods.